2003
DOI: 10.1046/j.1460-9592.2003.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Beat‐to‐Beat Left Heart AV Normalization:

Abstract: Programming the right heart AV interval to a normal value may cause a nonphysiological left heart AV due to interatrial and interventricular conduction delays, thus affecting cardiac performance. Since AV normalization at rest and exercise may be invalidated by pacing or sensing (mode) changes, the aim of this study was to (1) study the feasibility of a mode independent pacemaker (PM) algorithm for automatic beat-to-beat left AV normalization, (2) establish normal values for the time between mitral flow A wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
2
14
0
3
Order By: Relevance
“…The relation between P‐wave duration or interatrial conduction interval and optimal AV delay has been explained previously 25–27 . Optimal AV interval requires LV contraction to start soon after the completion of LA contraction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The relation between P‐wave duration or interatrial conduction interval and optimal AV delay has been explained previously 25–27 . Optimal AV interval requires LV contraction to start soon after the completion of LA contraction.…”
Section: Discussionmentioning
confidence: 94%
“…The timing of the LA contraction is determined by LA electrical activation, which is reflected in the final portion of the P‐wave during normal sinus rhythm or right atrial (RA) pacing 26 . Similarly, LV contraction occurs at a certain delay after LV activation, which starts shortly after the biventricular pacing 25 . Therefore, the interval from the end of the P‐wave to the biventricular pacing pulse is more directly related to LA‐to‐LV timing compared with the device AV delay, which represents RA‐to‐LV timing.…”
Section: Discussionmentioning
confidence: 99%
“…Several patient‐specific factors, such as conduction between the right and left atria as well as electro‐mechanical coupling, are responsible for this difference 9–11 . The optimal device AV delay can be determined by either accounting for these factors 12 or, alternatively, by iterating through a number of device settings and evaluating cardiac function at each. Earlier publications have indicated that interatrial conduction time (IACT), defined as the delay between the activation of the right and left atria, may be an important determinant of the optimal AV delay 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The optimal device AV delay can be determined by either accounting for these factors 12 or, alternatively, by iterating through a number of device settings and evaluating cardiac function at each. Earlier publications have indicated that interatrial conduction time (IACT), defined as the delay between the activation of the right and left atria, may be an important determinant of the optimal AV delay 12,13 . We have previously reported a positive correlation between IACT and optimal AV during atrial pacing 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Mode switching is another example of an over utilized algorithm that can have negative patient consequences. Mode switch studies have shown that inappropriate mode switching occurs anywhere from 9% to 38% of the time 42–56 . These occurrences can be especially detrimental to CRT patients where therapy delivery will be inappropriately withheld.…”
Section: Cardiac Rhythm Management Device Selection Position Statementmentioning
confidence: 99%